2017
DOI: 10.1002/eat.22659
|View full text |Cite
|
Sign up to set email alerts
|

Self‐admission to inpatient treatment for patients with anorexia nervosa: The patient's perspective

Abstract: The aim of the present study was to explore patients' experiences of participating in a self-admission program at a specialist eating disorders clinic. Sixteen adult program participants with a diagnosis of anorexia nervosa were interviewed at 6 months about their experiences in the self-admission program. A qualitative content analysis approach was applied to identify recurring themes. Four themes were identified: Agency and Flexibility, Functions, Barriers, and Applicability. Participants used self-admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 14 publications
1
37
0
Order By: Relevance
“…We therefore assess that our illustrative model and the established main concern about feeling safe and the circumstances that could affect this are essential when discussing the PCA programme. The concern for feeling safe is in line with what other studies have found (Olsø et al., 2016; Rise et al., 2014; Strand et al., 2017; Tytlandsvik & Heskestad, 2009) and may point to the fact that safety is particularly important for patients with a mental disorder, regardless of diagnosis. Studies regarding patient preferences during crisis also report that an available safe environment (Gudde et al., 2013) and being able to feel safe are important and helpful components (Klevan et al., 2017; Winness et al., 2010).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We therefore assess that our illustrative model and the established main concern about feeling safe and the circumstances that could affect this are essential when discussing the PCA programme. The concern for feeling safe is in line with what other studies have found (Olsø et al., 2016; Rise et al., 2014; Strand et al., 2017; Tytlandsvik & Heskestad, 2009) and may point to the fact that safety is particularly important for patients with a mental disorder, regardless of diagnosis. Studies regarding patient preferences during crisis also report that an available safe environment (Gudde et al., 2013) and being able to feel safe are important and helpful components (Klevan et al., 2017; Winness et al., 2010).…”
Section: Discussionsupporting
confidence: 84%
“…The first PCA initiative, a Norwegian study, found that patients value the right to decide when to be admitted (Tytlandsvik & Heskestad, 2009). Two other studies found that patients value the possibility to forestall the need for prolonged hospitalisations (Olsø et al., 2016; Strand et al., 2017). Patients also perceived that the health service differed substantially from earlier experiences of inpatient care (Olsø et al., 2016; Rise et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about the role of SDM in the treatment of anorexia nervosa or eating disorders more generally [ 45 ▪ , 46 ]. In 2019, Himmerich et al [ 45 ▪ ] stated that the treatment of eating disorders could benefit from SDM, as it aims to improve care by encouraging the production and dissemination of information and increasing patient participation.…”
Section: Shared Decision-makingmentioning
confidence: 99%
“…Specifically, the melanopsin containing intrinsically photosensitive retinal ganglion cells (ipRGCs) with a peak sensitivity to narrowband light mediate a sustainment of the pupillary contraction beyond termination of a blue light stimulus, the so-called postillumination pupillary response (PIPR). In both human and animal studies, the ipRGCs have been shown to be a prominent effectors of the non-image-forming visual functions (NIF) such as circadian homeostasis, mood and alertness and melatonin suppression (5).…”
Section: Investigations Of Pupillary Responses In Depressionmentioning
confidence: 99%
“…It might be that the most severely ill patients are less likely to be able to make use of the model in a constructive manner, due to lack of insight or reduced capacity for independent decision-making in times of exacerbated illness. For example, in our pilot self-admission project for patients with severe and enduring eating disorders, the ambivalence inherent to these disorders has often hindered optimal use of the model (5). To avoid crowding out effects, proper health economics analyses must be performed before scarce healthcare resources are allocated to a highly select group of patients on a larger scale.…”
mentioning
confidence: 99%